Pembelajaran Kekhasan Atom Karbon Untuk Membentuk Karakter dan Hasil Belajar Siswa di SMK Negeri 1 Tolitoli - Badwi Badwi; Suherman Suherman; Solfarina Solfarina (Universitas Tadulako, 2015)
The characters of students can be developed through a learning process integrated to the subjects of chemistry on the distinctiveness of carbon atoms with stimulus on the achievement of learning outcomes in cognitive, affective, and psychomotor aspects through cooperative method of STAD (Student Teams Achievement Division) type. This study analysed and described: (1) effect of learning the distinctiveness of carbon atoms charged characters to develop characters of students at SMK Negeri 1 Tolitoli; (2) effect of learning the distinctiveness of carbon atoms charged characters to the learning outcomes of students at SMK Negeri 1 Tolitoli; (3) effect of characters to the learning outcomes on learning the distinctiveness of carbon atoms at SMK Negeri 1 Tolitoli. This study used a quasi-experimental method. The samples was whole classes of X CEN (Computer Engineering and Networks) consisting of class X CEN1 with 32 students as an experimental group, and class X CEN2 with 34 students as a control group, which were determined by purposive random sampling technique. The data were collected using questionnaires, tests, interviews and observation sheets. The data were analysed using t-test with the significance level α= 0.05. The results showed that (1) learning the distinctiveness of carbon atom charged characters affected to develop characters of students at SMK Negeri 1 Tolitoli showed by significance value (0,000) < α (0,05); (2) learning the distinctiveness of carbon atom charged characters affected to the learning outcomes of students at SMK Negeri 1 Tolitoli showed by significance value (0,000) < α (0,05); and (3) the characters affected to the learning outcomes on learning the distinctiveness of carbon atoms at SMK Negeri 1 Tolitoli showed by significance value (0,005) < α (0,05).